Individual and Sociolinguistic Differences in Language Background Predict Stroop Performance - Freeman, Max R.; Robinson Anthony, Jonathan J. D.; Marian, Viorica; Blumenfeld, Henrike K. (Frontiers in Communication, 2022)
To examine how differences in language experience and sociolinguistic context impact cognitive control, 146 Spanish-English bilingual participants were tested on a nonlinguistic Stroop arrows task. Dimensions of language experience included a continuum of L2 proficiency, exposure, age of L2 acquisition, and English receptive vocabulary, along with cognitive nonverbal reasoning. Sociolinguistic context varied with more exposure to Spanish for participants in Southern California (SoCal) than in the Midwest. The task involved perceptual stimulus-stimulus conflict within stimulus features (e.g., right-pointing arrow on the left side of a display). Reaction times to trials where arrow location and direction matched (congruent), mismatched (incongruent), or arrow location was centered (neutral) were used to calculate Stroop (incongruent-congruent), facilitation (neutral-congruent), and inhibition (incongruent-neutral) effects. When examining performance on a continuum of bilingual language experience, individual differences in linguistic background (i.e., L2 proficiency and exposure, receptive vocabulary) and cognitive abilities (i.e., nonverbal reasoning abilities) predicted more efficient performance on the Stroop task. Across sociolinguistic contexts, findings revealed better performance via smaller Stroop and facilitation effects in the Midwest than in SoCal, and no group difference on the inhibition effect. We conclude that research on the cognitive consequences of bilingualism must consider a continuum of language experiences and must be situated in broader naturalistic contexts that take into account the sociolinguistic environments of language use.